Revisiting the determinants of students' performance in an undergraduate accountancy degree programme in Singapore - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2012)
This study investigates the association of prior academic achievement, admission interview, critical thinking, mathematical aptitude, gender and age with successful academic performance in an undergraduate accountancy degree programme at a Singapore university. The purpose of revisiting the determinants of academic performance is twofold: first, university accounting education in Singapore has changed greatly since Koh and Koh’s earlier study (1999); this study examines if determinants previously identified as significant continue to be so in the new setting; second, the study tests the usefulness of admission interview in identifying applicants who achieve subsequent academic success. Data on students’ performance throughout the whole degree programme are obtained from the university students’ records database. Results indicate that prior academic performance, admission interview, critical thinking and gender are significantly associated with successful academic performance in the accountancy degree programme. However, mathematical aptitude and age are not significantly associated with successful academic performance.